2020
DOI: 10.1021/acsnano.0c06000
|View full text |Cite
|
Sign up to set email alerts
|

Microenvironment-Triggered Degradable Hydrogel for Imaging Diagnosis and Combined Treatment of Intraocular Choroidal Melanoma

Abstract: Human choroidal melanoma (HCM) is one of the most common primary intraocular tumors and easily provokes liver metastases owing to the lack of sensitive and noninvasive therapeutic methods. Concerning the imaging diagnostics and therapeutic predicaments for choroidal melanoma, we designed microenvironment-triggered degradable hydrogels (RENP-ICG@PNIPAM:Dox-FA) based on ultrasmall (<5 nm) rare-earth nanoparticles (RENPs) with enhanced NIR-II luminescence. The ultrasmall diameter can significantly enhance the NIR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 61 publications
0
25
0
Order By: Relevance
“…ICG can also improve photothermal therapeutic effects by incorporating rare-earth nanoparticles (Ln: 72% Y 3+ , 20% Yb 3+ ,8% Tm 3+ ) via electrostatic adsorption. Li et al recently created an ICG–rare-earth nanoparticle-loaded hydrogel, with the successful implementation of NIR-triggered release of adriamycin (DOX) [ 92 ].…”
Section: Composition Of Hydrogels With Photothermal Effectsmentioning
confidence: 99%
“…ICG can also improve photothermal therapeutic effects by incorporating rare-earth nanoparticles (Ln: 72% Y 3+ , 20% Yb 3+ ,8% Tm 3+ ) via electrostatic adsorption. Li et al recently created an ICG–rare-earth nanoparticle-loaded hydrogel, with the successful implementation of NIR-triggered release of adriamycin (DOX) [ 92 ].…”
Section: Composition Of Hydrogels With Photothermal Effectsmentioning
confidence: 99%
“…The degradability of the hydrogel composites under physiological conditions is conducive for alleviating long‐term biological toxicity and promoting a photothermal‐chemotherapeutic effect ( Figure 10 ). [ 85 ] Conversely, the biodegradability of nanomedicine remains a particularly important consideration in gene‐based therapies for repeated gene transfection. [ 86 ] Following cell uptake, nanocarriers need to escape intracellular compartments, such as endosomes and lysosomes, to sequentially unpack their gene payloads, such as pDNA and siRNA, via degradation.…”
Section: Fundamental Physicochemical Properties Of Ocular Nanomedicinementioning
confidence: 99%
“…They have been incorporated into biodegradable hydrogels based on PNIPAM dual response, which could release the drug in a controlled manner by responding to heat and glutathione in the tumor microenvironment. The nanocomposites were then further decorated with indocyanine green (ICS) and folic acid (FA) to enhance therapeutically and to target specificity and the possibility of achieving photothermal therapy [ 161 ]. A lot of studies showed the potential of therapeutic contact lenses in the management of eye disease [ 162 ].…”
Section: Fluorescent Nanosystems In Ocular Applicationmentioning
confidence: 99%